Of Luck Both Epistemic and Moral in Questions of Doping and Non-Doping - Kirkwood, Kenneth William (ETHICS IN PROGRESS, 2020)
This article is a case study of a question of possible doping and how our insights into our moral judgements about doping are subject to considerations of both moral, but more presciently, epistemic luck. The eternal ambiguity surrounding the prevalence of doping, and its impact on high-level sport make this question entirely relevant for our discussions about the ethics of performanceenhancement in sport.